PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DI UPTD PUSKESMAS HILIZALOOTANO KECAMATAN MAZINO KABUPATEN NIAS SELATAN - Riminiat Waoma (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
The purpose of this study was to determine the influence of leadership on employee performance at the UPTD Hilizalootano Health Center, Mazino District, South Nias Regency. The type of research used is a causal quantitative type, the population and sample in this study were all employees at the UPTD Hilizalootano Health Center, Mazino District, South Nias Regency, totaling 60 people. Data collection techniques are interview techniques, questionnaire techniques and documentation techniques. The data analysis method used is simple regression analysis. Based on the research results of testing the hypothesis with a tcount of 6.449> ttable 1.672, so that researchers can conclude that there is an influence of leadership on employee performance at the UPTD Hilizalootano Health Center, Mazino District, South Nias Regency. The suggestions for this research are (1) In order to carry out a good job in the sub-district office, preferably in the division of labor for employees it is necessary to adjust it to the profession and class. (2) In improving employee performance, as the leader of the organization, it is necessary to create a work environment to maintain harmonious communication between colleagues.